An integrated approach to the diagnosis and correction of osteoporotic changes in postmenopausal women - I S Zakharov; G I Kolpinskiy; G A Ushakova; G V Wavin (IP Berlin A.V., 2015)
In the present study the possible comprehensive diagnosis and correction processes of bone resorption associated with postmenopausal osteoporosis are identified, given the markers of oxidative stress. The predictive role of MDA, SOD and catalase in the development of osteoporotic changes was evaluated. A single-blind, randomized, placebo-controlled study evaluating the efficacy of antioxidant complex SeltsinkR plus was held. Antioxidant course correction for 6 months significantly reduced the concentration of MDA (p=0.002) and increased the activity of SOD (p=0.001) compared to placebo. At the same time significantly reduced urine deoxypyridinoline indicators (p=0.03) is a marker of bone resorption process.